(untitled) (Ágora de Heterodoxias, 2024)
This document presents a synthesis of the model of thought and action, from the perspective of living systems, such as those that characterize the natural activity of human beings and organizations, called Planning System in a Systemic Approach: SISPLANES© (its acronym in Spanish). Planning is defined as an action preceded by reflection as an integrated whole that has emotion as a key factor. In other words, planning is conceived as a process inherent to the human being and its expression in organizations configured based on the functioning pattern of beings (living systems) which has been called the "systemic view of life". The fundamental contributions of SISPLANES© are to design a relational model for planning as an organic whole, in which action is preceded by reflection based on "emotion", defined under the principles of functioning of living systems, with which a scheme is configured of work for action, defining its organizational modality and its instruments (toolbox). The conceptual framework that supports the model and work regime is presented, as well as its particularities and dynamics, management philosophy and benefits. For more information, see: http://sisplanes.com